Ethnic disparities in the incidence of gynecologic malignancies among Israeli Women of Arab and Jewish Ethnicity: a 10-year study (2010-2019) - Roie Alter; Adiel Cohen; Paul-Adrien Guigue; Raanan Meyer; Gabriel Levin (SAGE Publishing, 2024)
Background: Ethnic disparities in healthcare outcomes persist, even when populations share the same environmental factors and healthcare infrastructure. Gynecologic malignancies are a significant health concern, making it essential to explore how these disparities manifest in terms of their incidence among different ethnic groups. Objective: To investigate ethnic disparities in the incidence of gynecologic malignancies incidence among Israeli women of Arab and Jewish ethnicity. Design: Our research employs a longitudinal, population-based retrospective cohort design. Method: Data on gynecologic cancer diagnoses among the Israeli population from 2010 to 2019 was obtained from a National Registry. Disease incidence rates and age standardization were calculated. A comparison between Arab and Jewish patients was performed, with Poisson regression models being used to analyze significant rate changes. Results: Among Jewish women, the age-standardized ratio (ASR) for gynecologic malignancies decreased from 288 to 251 ( p  < 0.001) between 2014 and 2019. However, there was no significant change in the ASR among Arab women during the same period, with rates going from 192 to 186 ( p  = 0.802). During the study period, the incidence of ovarian cancer decreased significantly among Jewish women ( p  = 0.042), while the rate remained stable among Arab women ( p  = 0.102). A similar trend was observed for uterine cancer. The ASR of CIN III (Cervical Intraepithelial Neoplasia Grade 3) in Jewish women notably increased from 2017 to 2019, with an annual growth rate of 43.3% ( p  < 0.001). A similar substantial rise was observed among Arab women, with an annual growth rate of 40.5% ( p  < 0.001). In contrast, the incidence of invasive cervical cancer remained stable from 2010 to 2019 among women of both ethnic backgrounds. Conclusion: Our findings indicate that Arab women in Israel have a lower incidence rate of gynecologic cancers, warranting further investigation into protective factors. Both ethnic groups demonstrate effective utilization of cervical screening.